Pengaruh Iklan, Harga dan Kualitas Layanan Terhadap Keputusan Pembelian - Andi Irwin; Ana Yuliana; Nur Asmi Azis; Hasirah; Sri Karuniari Nuswardhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the business world, it is increasingly developing, where the rapid development also experiences continuous metamorphosis. The development of the business also results in changes in the patterns and ways of competitors in maintaining their business. This study aims to determine the Influence of Advertising, Price and Service Quality on Purchasing Decisions. The current analysis uses a quantitative approach. The population of this study are consumers or customers who have purchased goods or services on purchasing decisions. Samples were taken from the population, and the selection of this research sample was determined by random sampling to produce a sample of 150 respondents. The results of the study found that the variables of advertising, price and service quality influence purchasing decisions.